ACTUAL QUESTIONS OF PATHOMORPHOLOGYCAL STUDY OF GASTROPATHIES INDUCED BY NONSTEROIDAL ANTIINFLAMMATORY DRGUGS - Вернигородський, С.В. (World of Medicine and Biology, 2014)
The pathogenetic links and pathomorphological changes of a gastric mucosa (GM) arising in gastropaties induced by nonsteroidal antiinflammatory drugs and antiaggregants were analyzed. The mechanisms of antisecretory drugs influence on GM were investigated.